Exploring Ethics: Understanding the Role of Privacy Policies and Institutional Review Boards in Digital Health Companies - Jacqlyn L Yourell; Kelsey L McAlister; Clare C Beatty; Jennifer L Huberty (Journal of Medical Internet Research)
AbstractResearch efforts are growing rapidly in the digital health industry, but with this growth comes increasing ethical challenges. In this viewpoint paper, we leverage over 20 years of combined experience across academia, industry, and digital health to address critical issues related to ethics, specifically privacy policies and institutional review board compliance, which are often misunderstood or misapplied. We examine the purpose of privacy policies and institutional review boards, provide brief examples where companies faced legal and ethical consequences due to shortcomings, and clarify common misconceptions. Finally, we offer recommendations on how digital health companies can improve their ethical practices and ensure compliance in a rapidly evolving landscape.